(untitled) (Historia, 2021)
Although a brief, but perspective biography of Dirk Mudge, based on considerable research, appeared in Afrikaans in 1999, it was good to hear that Mudge, the most important internal leader in the process leading to Namibia’s independence, had followed other Namibian politicians and written his memoirs. First published in Afrikaans in 2015, these now appear in an English translation, with a Preface by Piet Croucamp. Though some of his Preface makes no sense, one can agree with Croucamp the Mudge "contributed more than most to leading those on the inside into a brave new world called "democracy" (p.15).